Role of gender, professional level, and geographic location of artists on how they represent a story: the case of Little Red Riding Hood (UNED Research Journal, 2017)
Little Red Riding Hood is a widely known classic story and its text has been abundantly analyzed, but no detailed statistical stud- ies have been published about how it has been illustrated. We analyzed 554 images from the public artists’ site DeviantArt (January, 2015); clas- si ed them according to how the wolf, Little Red, and the environment were represented by the artists; and applied non-parametrical statisti- cal tests to check several hypotheses. When compared with profession- als, amateur artists tended to present a more neutral environment, and to humanize the wolf. Female artists were more likely to represent the wolf as a dressed man. Men were more likely to set the story outside of forests, to eroticize Red and to show her confused, scared or unin- terested when rst meeting the wolf. The neutral attitude of amateurs towards nature suggests indecision, while professional artists seem more used to produce family-friendly images. The female tendency to present the wolf as a man forces them to dress him and may re ect a stronger awareness about the moral of the story, meant to warn young women about men’s sexuality. Men deviate more from the forest set- ting because they feel safer in new environments, and also appear to see Red as a sexually attractive partner and the wolf as a competitor. Artists tended to show no sexual intent between the characters, but those who did were mostly amateurs. The global similarity in art about Little Red Riding Hood indicates that all modern audiences are familiar with the standard representation of the story in books, lms and televi- sion. This article presents a rigorous quantitative approach to the study of art that can be applied to many other stories and subjects.
Keywords: artistic interpretation; cultural differences; effect of gender on art; fairy tale representation